Modeling the Pilot Injection and the Ignition Process of a Dual Fuel Injector with Experimental Data from a Combustion Chamber Using Detailed Reaction Kinetics - Frühhaber, Jens; Peter, Andreas; Schuh, Sebastian; Lauer, Thomas; Wensing, Michael; Winter, Franz; Priesching, Peter; Pachler, Klaus (International Powertrains, fuels & lubricants meeting SAE, 2018)
The introduction of the so called Emission Controlled Areas within the IMO Tier III legislation forces manufacturers of maritime propulsion systems to adherence to stringent emission thresholds. Dual fuel combustion, which is characterized by the injection of a small amount of fuel oil to ignite a premixed natural gas air mixture, constitutes an option to meet this target. At high diesel substitution rates and very short pilot injection events, the injector is operated in the ballistic regime. This influences spray penetration, mixture formation and ignition behavior. In the present work, a seven-hole dual fuel injector was measured in a combustion chamber to provide data for the generation of a CFD model using the commercial code AVL FIRE®. The liquid and the vapor phase of the fuel spray were quantified by Mie-scattering and Schlieren-imaging technique for different chamber conditions. Based on the measured spray characteristics, a methodology was developed to imprint a velocity profile to the initial droplets in the CFD model, to depict the spray penetration for small injection durations. To characterize the ignition process and the flame propagation, measurements of the OH* emission and the natural luminosity of the flame were carried out. A detailed reaction mechanism, which is able to predict both diesel and dual fuel combustion, was integrated in the CFD model. The ignition delay was fitted to the experimental data by adapting the reaction mechanism for different chamber temperatures. The influence of the presence of natural gas on the ignition behavior was validated using data from a rapid compression machine. Even for low temperatures and high pressures, similar to the start of injection under engine operating conditions, a good correlation could be achieved. The developed knowledge will be transferred to an engine model to investigate the limits of dual fuel combustion processes.<br